Experimental investigation of the thermal behavior of semi-solid materials - Mustafa, Omar Abdulhadi; Abedalh, Ayad Suleiman; Alkhaffaf, Zainab H. (Zielona Góra: Uniwersytet Zielonogórski)
In recent years, the problem of solid waste has increased due to the growing population and its needs and solid waste disposal is a severe and widespread problem in both urban and rural areas in many developed and developing countries. Waste recycling is one of the effective solutions to clean the environment.
Keywords: thermal conductivity; sawdust; waste paper; waste of PVC plastic; fumed silica; thermal energy